Modernization of Timber House in Felcra Changkat Lada, Perak - Jama, NUR ADIILAH; RAMELE RAMLI, ROHASLINDA (Research in Management of Technology and Business, 2024)
The Malaysian government intends to develop rural areas as the primary focus of the nation's economy, strengthen the agricultural sector, increase the quality of life, and reduce the difference between urban and rural residents' standard of living. With an effect on the rural economy, social structure, environment, and technology, it works to modernise the village while also enhancing the standard of living for rural residents. Rapid economic and urbanisation led to modernization of the timber housing sector. The development of new housing typologies in the various medium and high densities housing categories within the townships was carried out to meet new social and economic needs. The housing structures were utilising modern materials and technology in the functionalism architectural style, adjusted for the tropical environment. Therefore, this study aims to identify urbanization happened in one of the planned rural settlements in Malaysia: FELCRA Changkat Lada, Perak, by revealing the modernization of the timber houses, factors influencing the modernization, and strategies to preserve the identity of FELCRA village houses, while supporting the rural development efforts by the government. The study found that majority of timber houses in the village had practically demolished all of the original structures and many timber houses have been losing their original characters and identities as a FELCRA village house, due to current demands, changes in way of life, and challenges in maintenance.